Efficacy and safety of novel carbapenem–β-lactamase inhibitor combinations: Results from phase II and III trials - Yu, Wei; Shen, Ping; Luo, Qixia; Xiong, Luying; Xiao, Yonghong (Frontiers in Cellular and Infection Microbiology, 2022)
Objectives: The addition of the novel β-lactamase inhibitors to carbapenems restores the activity against multidrug resistant Gram-negative bacteria. The aim of this study is to summarize the evidence on efficacy and safety of novel carbapenem-β-lactamase inhibitor combinations. Methods: We conducted a meta-analysis of clinical trials comparing novel carbapenem-β-lactamase inhibitor combinations with comparators to assess the clinical and microbiological response, mortality, and adverse events (AEs). Results: A total of 1984 patients were included. The pooled risk ratio (RR) of clinical cure, microbiological eradication, all-cause mortality, and 28-day mortality were 1.11 (95%CI: 0.98-1.26), 0.98 (95%CI: 0.82-1.16), 0.90 (95%CI: 0.49-0.94) and 0.68 (95%CI: 0.49-0.94) between novel carbapenem-β-lactamase inhibitor combinations and control groups. Sensitivity analysis revealed phase II trial of imipenem-cilastatin/relebactam (ICR) against complicated urinary tract infections could be the most important factor of heterogeneity for microbiological response. The therapeutic effect of novel carbapenem-β-lactamase inhibitor combinations was better in meropenem-vaborbactam (MEV), phase III trials, and number of patients less than 200. The RR of AEs from any cause and serious adverse events (SAEs) for patients receiving novel carbapenem-β-lactamase inhibitor combinations were 0.98 (95%CI: 0.93-1.04) and 1.01 (95%CI: 0.75-1.36), respectively. Conclusions: ICR and MEV were superior to comparators for clinical cure and survival rate in treatment of complicated infections, and both were as tolerable as comparators.